How to close a colpotomy? Barbed suture and conventional suture eVects on soft tissue: An ex vivo pilot study - Chenchit Chayachinda (2018)
Objective To evaluate the eVects of diVerent suture materials and techniques on soft tissue in relation to deWned tensions and time points. Materials and methods Two bovine intestine samples, 4 £ 4 cm size and 3 mm thickness, were adapted with interrupted and continuous techniques using three types of suture materials: Vicryl (polyglactin 910), PDS II (polydi-oxanone), and V-Loc 180 (knotless, barbed polyglyconate). Four stitches or loops 9 mm apart with three knots, and 10 mm end length were performed by one gynecologist. Forces were applied from 6 newtons (N) to 14 N continuously. Outcome measures included breakage of tissue, tearing of thread, and shortening of the end length of thread. They were evaluated immediately and then at Wrst, third, and Wfth minute. Results Tissue breakage using No. 3/0 suture materials appears in the applied force from 10 N. polydioxanone causes more tissue tearing than polyglactin 910. The least to withstand tension is knotless polyglyconate. Interrupted stitches hold the sutured sites better than continuous stitches in all groups of threads. Shortening of the knotless polyglyconate end length by half took place with 6 N force. Conclusion Simulating reparation of colpotomy, the ex vivo study supports that polyglactin 910 appears better in holding soft tissue than polydioxanone and knotless poly-glyconate. © 2012 Springer-Verlag.